The relationship between food intake and predation risk in migratory caribou and implications to caribou and wolf population dynamics - Heard, Douglas C.; Williams, T. Mark; Melton, Derek A. (Rangifer, 1996)
We examined the hypothesis that spring migration in barren-ground caribou (Rangifer tarandus) enhances access to high quality food, reduces predation risks or both. We related our findings to the hypothesis that one of the consequences of migration is that prey populations cannot be regulated by predation because predators are unable to respond numerically to changes in abundance of migratory prey. In the Northwest Territories, migration to calving grounds by pregnant cows reduced the risk of predation on neonates. Wolf (Canis lupus) densities on calving grounds averaged only 22% of winter range densities because most wolves denned near tree line. The quality and quantity of food that was available to cows that migrated to calving grounds was lower than for bulls and other caribou that lagged far behind the pregnant cows during spring migration. Fecal nitrogen levels were higher in bulls than in cows in late May and early June but there were no differences in mid or late June. Areas occupied by bulls in late May had a greater biomass of live sedges than on the calving ground in early June. It appears that although food in July is abundant and nutritious, insect harassment prevents efficient feeding. Body fat reserves in both sexes declined to almost zero by mid-July, the lowest level of the year. Insect numbers declined in August and body fat levels increased to the highest level of the year by early September. Because the timing of caribou's return to the hunting ranges of tree line denning wolves was related to caribou density, our data were inconsistent with the suggested consequence of migration. Tree line denning by wolves and density-dependent changes in caribou migration suggests a mechanism for population regulation in caribou and wolves. We suggest that the process is as follows; when caribou numbers increase, some density-dependent factor causes range expansion in August (e.g., competition for food) causing caribou to return earlier to the hunting ranges of tree line denning wolves, more denning wolves have access to caribou, wolf pup survival increases and wolf numbers increase. The effect on caribou population growth will depend on the timing and magnitude of the wolf numerical response.